How to prevent skin damage from air pollution. Part 1: Exposure assessment - Damevska, Katerina; Boev, Blazho; Mirakovski, Dejan; Petrov, Andrej; Darlenski, Razvigor; Simeonovski, Viktor (Wiley, 2020)
Both epidemiological and experimental studies have demonstrated the crucial connection between air pollution exposure and skin disorders. The exact mechanisms by which air pollutants mediate skin damage remain largely unknown. Therefore, it is very necessary to investigate the mechanism of air pollution-induced skin damage and explore some potential protective and therapeutic methods. In this review, we focus on the qualitative and quantitative skin exposure assessment methodologies-a relatively new field of interdisciplinary research.
Keywords: air pollution; skin